Critical factors for transferring and sharing tacit knowledge within lean and agile construction processes. Issue 1 (5th December 2017) - Saini, Mandeep; Arif, Mohammed; Kulonda, Dennis J.
Abstract : Purpose: The purpose of the paper is to investigate the critical success factors (CSFs) associated with the effectiveness of transfer and sharing of tacit knowledge in lean and agile construction processes. Design/methodology/approach: The study identifies ten CSFs that initiate the transferring and sharing of tacit knowledge. The CSFs are validated through quantitative study. This study recruited project managers, executives, consultants and other managers that are directly involved in the management of a construction project. It recruits the respondents those have background and experience from disciplines such as lean construction, agile construction, construction supply chain (CSC) and knowledge management in lean, agile and CSC. The data collected through self-administrative questionnaire are categorised as ordinal data to analyse in SPSS with frequency and Kruskal–Wallis H test, Spearman's correlation analysis and a rank-order analysis is done to establish the level of importance of those factors. Findings: Initially, "Trust between construction organisations" is identified as the foremost CSF. Moreover, other CSFs such as motivation, leadership capabilities, business strategies and organisational capabilities follow trust. Originality/value: This is the first study that investigates and establishes the CSFs that are essential to initiate transferring and sharing tacit knowledge in a lean and in an agile construction processes.